Effects of Find Thirty every day: Cross-Sectional Findings From a Western Australian Population-Wide Mass Media Campaign, 2008-2010 - Leavy, Justine; Rosenberg, M.; Bauman, A.; Bull, F.; Giles-Corti, B.; Shilton, T.; Clover, M.; Barnes, R. (Sage Publications, 2012)
Background: Internationally, over the last four decades large-scale mass media campaigns have been delivered to promote physical activity and its associated health benefits. In 2002-2005, the first Western Australian statewide adult physical activity campaign Find Thirty. It’s Not a Big Exercise was launched. In 2007, a new iteration of the campaign was proposed with new objectives, executions, and tag line Find Thirty every day®. Purpose: This article reports on the population-level effects of the Find Thirty every day® campaign from 2008 to 2010, with a focus on changes in awareness, intention, and physical activity. Methods: Evaluation of the campaign involved pre- and posttest serial cross-sectional surveys. Baseline data were collected in May 2008, and subsequent surveys in 2009 and 2010. Samples sizes were as follows: baseline (n = 972), first follow-up (n = 938), and second follow-up (n = 937). Data were derived from self-reported responses to a random-sample computer-assisted telephone interview. Results: Total awareness increased from 30.4% at baseline to 48.5% at second follow-up. Total awareness was higher in women and low socioeconomic status adults. Intention was 21.0%, double that reported at baseline. There were positive significant changes from baseline to first follow-up across all four categories: walking, moderate, vigorous, and total physical activity. There also were positive significant changes for self-reported walking from baseline to second follow-up. Conclusion: Find Thirty every day® resulted in an increase in awareness, intention, walking, vigorous intensity, and total level of physical activity in priority target groups. Campaign effects should be further examined by subgroups to identify the most receptive population segments.